PEMANFAATAN LINGKUNGAN SEKITAR SEBAGAI SUMBER BELAJAR IPS DI SEKOLAH DASAR - Ratu Lailatunnufus; Siti Nurfadilah; Irpa Septiyani; Susi Dianawati; Nurjanah; M. Andriyana Muhsinin; Dine Trio Ratnasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to provide a comprehensive examination of how the surrounding environment can be utilized as a learning resource in Social Studies (IPS) at the elementary school level. Beyond discussing theoretical foundations, this research also offers practical guidelines for teachers to design learning activities that are more contextually relevant to students’ real-life situations. Using a literature review approach, the study compiles various references that highlight the effectiveness of environmental-based learning and its contribution to improving the overall quality of instruction. The findings reveal that students’ engagement significantly increases when the local environment is integrated into the learning process. Activities such as direct observation, exploring social conditions in the community, and examining geographical phenomena make the learning experience more dynamic and meaningful. Students gain a deeper understanding of the material because they can connect academic concepts to real situations they encounter daily. However, several challenges arise, including limited instructional time, insufficient supporting facilities, and varying levels of teacher readiness in implementing environment-based learning. These obstacles can be addressed through careful planning, strong institutional support, and collaboration with the local community. Overall, this study emphasizes that incorporating the environment as a learning resource can create a more interactive and student-centered classroom atmosphere. This approach not only enhances students’ comprehension but also fosters critical thinking, creativity, and social awareness. With consistent application, environment-based learning has the potential to offer substantial benefits for students, teachers, and the broader community.